Various Forms and Meanings of Diminutive in Classical and Modern Arabic - Aziz, Abdul; Gunawan, Riski; Anwar, Saepul (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
Diminutive (isim tasgĩr) is often interpreted in Arabic as a word that means 'little'. In fact, linguistic data shows the many meanings denoted and connoted by this diminutive form and meaning. Hence, this study aims to describe various forms and meanings of diminutive lexemes in Arabic. Diminutive is a small form of a word which in Arabic is often referred to as isim tasgĩr. The method which is used is descriptive-qualitative. The source of research data are Arabic dictionaries, poetry collections and novels. The results of this study indicate: first, diminutive in Arabic if it is seen in its form has one morpheme, namely u ay, with three different realizations depending on the number of consonants of a word, i.e. when the lingual unit (adjective or noun) is minimized consists of three consonants, u ay i when the lingual unit (adjective or noun) is divided consisting of four consonants and u ay iy, with several omissions of several consonants when the lingual unit both the noun and the adjective are divided into five consonants or more; secondly, it is diminutive in Arabic if it is seen as the meaning that shows affection, closeness, intimacy, insulting or looking down, praising and others. The significance of this research based on the presentation of other meanings which are not only of 'smallness' or 'littleness' of its meaning. This study at least has a novelty about adding other meanings that is broader than just a small meaning in Arabic.